The European Art Market in the Twentieth Century: A Review of Studies on Art as Capital and Property - Alvi, Maddalena (History compass, 2026)
Art embodies material and symbolic value; it is a source of intellectual and cultural nourishment, a marker of social status, a symbol of national dignity, private or public property. Yet, art is also a commodity—one that has shaped and been shaped by a long and complex history: that of the art market. This article examines the twentieth-century art trade as a crucial area for historical inquiry, offers a review of existing scholarship in the field, and addresses the issue of its historicisation. It engages with contributions from external disciplines (economics, sociology, anthropology, art history) and various sub-fields within history (political, cultural, and social histories) that have contributed to the study of commercial and cultural dynamics and the evolution of art markets. To make sense of this interdisciplinary field, this paper proposes a framework based on the notion that art is the crucible of property and capital. This lens provides a valuable perspective to contextualise the trade in the history of twentieth-century Europe and to use the market as a source to understand developments in European cultural, social, and economic history.